2021
DOI: 10.1055/s-0041-1732491
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of CD34, CD117, and p53 in Hypocellular Bone Marrow Disorders

Abstract: Objectives Hypocellular bone marrow (BM) disorders comprise heterogeneous entities associated with peripheral cytopenias and decreased production of hematopoietic cells in BM. This study was undertaken to analyze immunohistochemical expression of CD34, CD117, and p53 in morphologically diagnosed patients of hypocellular BM (aplastic anemia [AA], hypocellular myelodysplastic syndrome [h-MDS], and hypocellular acute myeloid leukemia [h-AML]). Materials and Methods BM specimens were obtained from patients present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…13 The percentage of CD34+ cells in normal BMB does not exceed 1%, whereas abnormalities in both percentage and distribution of positive cells have been observed in MDS patients who have a tendency towards forming aggregates. 7,[14][15][16][17] Similarly, the high proportion of CD34+ cells and the high number of CD34 aggregates also can be observed in AML patients. 18 Sharma et al 7 reported that immunoexpression of CD34 was decreased in 25 (96.2%) patients of AA.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…13 The percentage of CD34+ cells in normal BMB does not exceed 1%, whereas abnormalities in both percentage and distribution of positive cells have been observed in MDS patients who have a tendency towards forming aggregates. 7,[14][15][16][17] Similarly, the high proportion of CD34+ cells and the high number of CD34 aggregates also can be observed in AML patients. 18 Sharma et al 7 reported that immunoexpression of CD34 was decreased in 25 (96.2%) patients of AA.…”
Section: Discussionmentioning
confidence: 91%
“…7,[14][15][16][17] Similarly, the high proportion of CD34+ cells and the high number of CD34 aggregates also can be observed in AML patients. 18 Sharma et al 7 reported that immunoexpression of CD34 was decreased in 25 (96.2%) patients of AA. However, the percentage of CD34+ cell was increased in hypo-AML and in all 3 (100%) patients of hypo-MDS.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations